Maqasid Al-Syari'ah Transformation in Law Implementation for Humanity - Tahir, Tarmizi; Hamid, Syeikh Hasan Abdel (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2024)
The needs of humanity, which is the goal of the Shari'a, never end. Maqasid Syari'ah, an approach to Islamic studies, is a benchmark in answering society's problems. Maqasid Syariah is required to continuously transform following developments in conditions and times to realize humanity's problems. This paper discusses the transformation of maqasid al-shari'ah in implementing law for humanity by revealing the following problems: (1) How is the transformation of maqasid al-shari'ah from traditionalism to contemporary? and (2) What are the opportunities for developing the concept of maqasid al-shariah in implementing law for humanity? The research method used in this paper is library research, which is a source of data and information through classic and contemporary books and several journals. Maqasid al-Syari'ah is the goal of the Shari'ah ordained by Allah SWT, namely, to realize the benefit of humans in this world and the hereafter. The benefit goal is included in maslahah daruriyyah, namely hifz al-din, hifz al-nafs, hifz al-aql, hifz al-nasl and hifz al-mal. In subsequent developments, contemporary ulama expanded the area of maqasid al-shari'ah not only to individual reach but also to reach social, environmental, and state areas. Likewise, the maqasid al-shari'ah paradigm has developed from a paradigm of protection and development to a paradigm of development and human rights. The opportunity for maqasid al-shari'ah transformation in implementing the law for humanity is to realize the development of maslahah daruriyyah in several sectors of human life, such as the environment, society, and the state. So that the daruriyah maslahah has been added, namely hifz al-bi'ah, hifz al-ummah and hifz al-daulah.